Expansion microscopy of mouse brain organotypic slice cultures to study protein distribution - Diane Bissen; Maximilian Ken Kracht; Franziska Foss; Amparo Acker-Palmer (STAR Protocols, 2022)
Summary: Assessing protein distribution with super-resolution in tissue is often complicated and restrictive. Here, we describe a protocol for immunostaining and expansion microscopy imaging of mouse brain organotypic slice cultures. We detail an Imaris analysis workflow to analyze the surface vs intracellular distribution of AMPA receptors at super-resolution during homeostatic plasticity. We have optimized the protocol for brain organotypic slice culture and tested in acute brain slices. This protocol is suitable to study protein distribution under multiple plasticity paradigms.For complete details on the use and execution of this protocol, please refer to Bissen et al. (2021). : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.